Impact of an online parenting support programme on children’s quality of life - Nunes, Cristina (2022)
The study aims to describe the parental use of an online parenting support programme, the ‘Open Window to Family’ (JAF) and to evaluate its impact on perceived children’s quality of life (QoL). This programme makes online resources available to support positive parenting. The study included 363 parents (nintervention group = 142) who completed measures to evaluate their children’s QoL. The results suggest that using the programme for a longer time and accessing more information/services are positively related to the perception of utility but not to the frequency of use. The programme proved to be more useful for specific difficulties and to search for specific information. We found high levels of parental perception of children’s well-being, both physical and psychological, and lower values in social support and relationships with peers. No differences were observed between the total QoL of children in the intervention group and control group. The differences in the dimensions of QoL are due to interaction with the level of education of the mother: mothers with higher education reported higher physical well-being, social support, relationships with peers, and school context. Guidelines are suggested to enhance the accessibility of this type of programme as well as enhance its impact on parents and children.